Juridical Study on the Criminal Acts of theft by Minors at the Surakarta - Supardi; Bastianto Nugroho; Supolo Setyo Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The purpose of this study is to analyze the punishment for the crime of theft committed by children. under age. The research method uses a normative juridical research method, which focuses on the study starting from the provisions of the applicable laws and regulations, accompanied by legal theories and principles related to the problems studied. The results of the study of the Juridical Study of the Criminalization Conducted by Judges Against the Crime of Theft Perpetrated by Minors in the Surakarta District Court based on Law No. 3 of 1997 concerning Juvenile Court. That the Surakarta District Court Judge has acted in accordance with the applicable laws and regulations, namely the Criminal Code, and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In making a decision, the judge will consider several things, namely: evidence, the fulfillment of the elements of a criminal act, aggravating and mitigating matters, and the presence or absence of excuses and justifications. From these considerations, the judge handed down a decision against the naughty child. The punishment carried out by the Surakarta District Court judge against minors who commit the crime of theft is still far from the maximum penalty that can be imposed, which is in accordance with Article 11 paragraph (1) of Law Number 3 of 1997.